Kompetensi Sosial Guru Pendidikan Kristen Berdasarkan Matius 23:4-12 dan Implikasinya di Sekolah Dasar Negeri 071095 Fukagambo - Desperius Gulo (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study aims to analyze the principles of social competence contained in Matthew 23:4-12 and how they are implied with the social competence of Christian Education Teachers (PAK Teachers) at SD Negeri 071095 Fukagambo. Matthew 23 provides criticism of the behavior of hypocritical teachers and in this context, is used as a basis for reflection to develop authentic social competence of teachers. The research method used is qualitative descriptive, with data collection techniques through literature secunder. The results of the study indicate that the understanding and application of the principles of Matthew 23:4-12 in the social competence of PAK Teachers at SD Negeri 071095 Fukagambo still vary. This study recommends the need for increased training and mentoring for PAK Teachers, as well as strengthening the understanding of social competence so that teacher errors according to Matthew 23 are not repeated.